2018
DOI: 10.1101/276923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous protection from ischemic brain injury by preconditioned monocytes

Abstract: Exposure to low dose lipopolysaccharide prior to cerebral ischemia is neuroprotective in stroke models, a phenomenon termed preconditioning. While it is well established that lipopolysaccharidepreconditioning induces central and peripheral immune responses, the cellular mechanisms modulating ischemic injury remain unclear. Here, we investigated the role of immune cells in the brain protection afforded by preconditioning and we tested whether monocytes may be reprogrammed by ex vivo lipopolysaccharide exposure … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…For example, there are typically small variations in survival between experimental cohorts that may relate to differences in animals provided by the vendor, variations in reagents used for the procedure, noise levels in the colony/surgical suite, etc. Additionally, the cannula implantation may have induced inflammation in the CNS causing inflammatory pre-conditioning, which is a known protective factor against ischemic brain injury (for example, see (Garcia-Bonilla et al, 2018). Furthermore, this experiment may have included insufficient group sizes for detecting survival.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are typically small variations in survival between experimental cohorts that may relate to differences in animals provided by the vendor, variations in reagents used for the procedure, noise levels in the colony/surgical suite, etc. Additionally, the cannula implantation may have induced inflammation in the CNS causing inflammatory pre-conditioning, which is a known protective factor against ischemic brain injury (for example, see (Garcia-Bonilla et al, 2018). Furthermore, this experiment may have included insufficient group sizes for detecting survival.…”
Section: Discussionmentioning
confidence: 99%
“… 94 Interestingly, the meninges were associated with neuroprotection following an ischemic stroke via preconditioned monocytes. 95 Low doses of the proinflammatory mediator lipopolysaccharide (LPS) before an ischemic injury induced protection after transient occlusion of the middle cerebral artery, a phenomenon known as preconditioning. 95 , 96 This effect was recapitulated by adoptive transfer of monocytes isolated from LPS-preconditioned mice.…”
Section: Immune Cell Populations Of the Meninges And Chpmentioning
confidence: 99%
“… 95 Low doses of the proinflammatory mediator lipopolysaccharide (LPS) before an ischemic injury induced protection after transient occlusion of the middle cerebral artery, a phenomenon known as preconditioning. 95 , 96 This effect was recapitulated by adoptive transfer of monocytes isolated from LPS-preconditioned mice. Specifically, the neuroprotective monocytes were recruited to meningeal vessels, where they dampened the expression of proinflammatory genes involved in the activation of neutrophils and chemotactic factors such as Csf3, 97 indicating an essential role of the meningeal compartment as a key immunoregulator in ischemic brain injury.…”
Section: Immune Cell Populations Of the Meninges And Chpmentioning
confidence: 99%
“…73 Some recent data revealed that while harmful role of Ly6C high and CCR2 + monocytes in adult stroke is well defined, immune preconditioning by low dose LPS protects adult mice from MCAO via induction of Ly6C high in monocytes and reprograming of gene expression in monocytes, with CCR2 playing an essential role in neuroprotection. 74 These data raise a possibility that the magnitude, the timing and the phenotypes of infiltrated and differentiated monocytes can be tuned to support long-term recovery but it is unknown whether similar scenario exists in injured juvenile brain. An improved understanding of leukocyte/neurovascular/microglial axis would shed light on how to enhance vascular remapping and brain connectivity after CAIS.…”
Section: Discussionmentioning
confidence: 99%